INFORMATION SERVICES: ACADEMIC PROCSTINATION, IMPACT AND TIME MANAGEMENT AS A PREVENTION AND MANAGEMENT STRATEGY - Susanti, Resti; Andriani, Riska; Marbun, Ruth (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
Procrastination has existed throughout human life. And until now it is still happening, especially academic procrastination among undergraduate and postgraduate students, therefore continuous efforts are needed to solve it. The number of student activities, both academic and non-academic, is the cause of the postponement of their coursework. To avoid procrastination or postponement of coursework, students must have good time management skills. The habit of postponing academic assignments is called academic procrastination. Students know the negative impact of procrastination behavior, procrastination can have an impact on students' academic achievement if left unchecked. One of the problems faced by students is academic procrastination, which can cause them to not be able to graduate on time.  By providing information services about causative factors, impacts, and time management as a strategy to handle and avoid academic procrastination in students at Griya Konseling Pancawaskita, the purpose of the implementation is to improve students' personal competence, because the survey results show that there are still students who have the habit of procrastinating related to academic assignments, which hinders their achievement.